Genetic detection and phylogenetic relationship of Babesia species infecting domestic dogs from select regions in Kenya - Ngoka, I.T.; Mbogo, K.; Kyallo, Martina M.; Oduori, D.O.; Pelle, Roger (Elsevier, 2021)
The genus Babesia has more than 100 species that are transmitted by ticks with some being zoonotic. They can infect humans, livestock, and wildlife. Although canine babesiosis occurs locally, published studies on the species involved are limited. Babesia parasites cause severe disease in dogs which can be fatal. Drawbacks of the current control methods necessitate vaccine development. The study objective was to identify the Babesia species infecting dogs from three Kenyan counties; Nairobi, Mombasa, Nakuru and determine their phylogenetic relationship. This will enable improved control and rule out zoonotic potential. The study period was October 2018 to November 2019.The study design was descriptive and sampling opportunistic. One hundred and forty-three dogs were sampled. From whole blood, total DNA was extracted using the TanBead extractor followed by PCR amplification targeting Babesia 18S rRNA. Positive samples were purified and sequenced using the Sanger Dideoxy method.CLC Genomics Workbench, GenBank™ and BLASTn™ on NCBI were used for sequence processing and analysis. Geneious prime™ was used for multiple sequence alignment and phylogenetic analysis. The overall prevalence of Babesia canis was 9.0% (95% CI: 4.37–13.81). Two out of 13 positive samples (2/13) were identified as Babesia canis vogeli, with a prevalence of 1.4% (95% CI: 1.38 - 14.2, n = 143) while 11/13 were identified as Babesia canis rossi, with a prevalence of 7.69% (95% CI: 3.3 -12, n = 143). The Babesia rossi sequences identified were closely related to sequences from black-backed jackals, while the Babesia vogeli ones were related to sequences from a pet cat in China. Babesia rossi which causes severe canine babesiosis was identified in 84.6% of the positive samples, immediate and aggressive clinical intervention is necessary. The possible sylvatic cycle of Babesia rossi and low levels of infections by Babesia vogeli should inform pertinent control measures.